The impact of consultant delivered care in paediatrics. (24th May 2012) - McColgan, MP; Edwards, H; Ewing, C; Winch, R
Abstract : Background: The RCPCH 2011 publication "Facing the Future" recommended the increased use of "resident consultants" and Sir John Temple's report "A Time for Training advocated consultant delivered care by arguing that consultants "make better decisions more quickly and are critical to reducing the costs of patient care while maintaining quality". However relatively sparse evidence exists to support these models of working. Aims: To assess the impact of consultant delivered services on: (1) outcomes in children's health; (2) training of junior doctors; (3) support for nursing and other health professionals; (4) admissions, length of stay, and other cost indicators (5) adherence to standards; (6) consultants' work/life balance; (7) development and retention of consultant skills. To develop models of effective service delivery using resident consultants; To identify service configurations where the models are most appropriate; To make recommendations on best practice, and how to implement the changes effectively. Methods: A questionnaire sent to all UK hospitals providing paediatric inpatient and/or neonatal care, followed by structured interviews at sites of interest. and detailed questionnaires sent to Findings analysed and assessed with stakeholder engagement. Results: 133 units (62.6%) responded to initial questionnaire: 24.6% have consultants on the middle grade rota; 48.5% have consultants doing resident twilight shifts; 96.3% operate consultant of the week systems; 99.3% have at least 1 consultant led handover per week; Conclusion: Approval for consultant delivered care amongst staff in units operating such models is high, but sustainability relating to age of consultants needs to be addressed. Strong opinion that the model provided good training and supervision.